The School of Business English - Lyudmila S. Pichkova (Vestnik MGIMO-Universiteta, 2014)
School of Business English prepare students for translation and abstracting economic texts, business correspondence and business communication originated in the late 1950s. Department of English Language № 2 pioneered the creation of the school of business English at MGIMO and made the largest contribution to its development. Developing and using the latest educational technology, actively participating in many innovative projects, responsive to changes in the economic and socio-political sphere and carefully studying the international experience, the Department has become the undisputed leader in language teaching profession. The emphasis is on the use of the advantages of a new method of object-language integrated learning, in which the program of teaching business English are built in close coordination with training programs on special subjects, and sometimes supplement them. Business games, round tables, student conferences in English have become long-term practice of the English Language № 2. Specialty permeates all stages and aspects of learning, including the common language practice.